Florence Fennel—Foeniculum vulgare var. azoricum (Mill.) Thell. - James M. Stephens (EDIS)
This document provides an overview of Florence fennel (Foeniculum vulgare var. azoricum), detailing its botanical characteristics, cultivation practices, and culinary uses. Grown successfully in Florida gardens, this aromatic plant features a bulb-like base used in cooking for its anise-like flavor. It thrives in cool weather and matures in about four months. The plant resembles celery and is often mistaken for dill, with thread-like foliage and a height of approximately three feet. Original publication date May 1994.